The Effects of Job Insecurity on Psychological Well-Being and Work Engagement: Testing a Moderated Mediation Model - Maria Leonor Pires (Behavioral Sciences, 2025)
In recent decades, there have been significant changes in employment relationships, leading to more precarious forms of employment and heightened perceptions of job insecurity. The purpose of this study was to test the effects of job insecurity on perceived psychological well-being and work engagement, with self-efficacy at work acting as a mediator and perceived supervisor support acting as a moderator. This study analyzed a sample of 938 individuals from Portugal who participated in the 2015 European Working Conditions Survey (EWCS). The results show that job insecurity has a negative impact on both psychological well-being and work engagement. Furthermore, the study found that self-efficacy at work acts as a mediator in the relationship between job insecurity, psychological well-being, and work engagement, with a buffering effect. Our results also show evidence of a moderation effect of perceived supervisor support, which works in two ways: perceived supervisor support amplifies the positive effect of self-efficacy at work on psychological well-being, as well as the indirect negative effect of job insecurity. However, this moderation effect was not observed in the relationship with work engagement. These results emphasize the significance of job insecurity regarding individual mental health and job-related attitudes, taking into consideration individual and organizational resources.